Moderated mediation role of ethnicity on natural skin care products purchasing intention model among multicultural consumers - Najm, Ahmed Abdulkareem; Salih, Sarah Abdulkareem; Fazry, Shazrul; Law, Douglas (Public Library of Science, 2024)
The trends for sustainable lifestyle and marketing motivated natural product consumption, such as natural skin care products (NSCPs). Different personal, environmental, and sociocultural factors influence purchase intention (PI) for NSCPs. However, there is a lack of evidence on the role of consumers’ ethnicity in the PI model. The present study investigated the moderated mediation role of ethnicity in the relationship between related factors, including environmental concern, subjective norms, health factor, Halal certificate, packaging design, past experience factor, price factor, and PI mediated by personal attitude. A web-based survey was utilized to capture quantitative data from a random sample of 330 multicultural consumer group participants. The results of the study indicated that consumers’ ethnicity substantially moderated the mediation effect of personal attitude in the relationships between subjective norms, health factor, Halal certificate, packaging design, past experience factor, price factor, and PI in the model. The findings contributed to understanding of the factors that influenced the PI of consumers from diverse sociocultural contexts in the market for natural products. It contributed directly to natural product marketing and industry.